The Application of Ecclesiology in Matthew: from the perspective of paradigm shift in Matthew 16: 13-20 and 18: 15-18 - JIANG, Tian (中国基督教研究（ISSN：3068-479X）, 2025)
In the four Gospels, only Matthew mentions churches. He connects it with Peter, authorities, and church discipline. It is also only Matthew that records the single speech about the church in Jesus' lifetime, which started a paradigm shift from the ἐκκλησία in the OT to the church in the NT. Meanwhile, the church became the formal embassy of God's kingdom after the Messiah ascended to heaven. The church community rule represents the authority of the church. Understanding the church's character in Matthew will help us catch a glimpse of the church's origin in the first century. Matthew emphasizes the authority of the church rather than the pastoral or any other functions of the church－this emphasis on authority also connects with the whole motif of Matthew. According to the paradigm-shifting role of Peter and the community discourse in Matthew, the "binding and loosing" authority of the church is church discipline. The center of church discipline is about forgiveness and reconciliation, and the discipline is not only applicable for individuals but also the church as the whole－the entire leadership.